2012
DOI: 10.1136/emermed-2011-200388
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making by ambulance clinicians in London when managing patients with epilepsy: a qualitative study

Abstract: Decisions regarding conveyance of patients with epilepsy in this study were substantially guided by ambulance clinician experience rather than by robust training and guidelines. This study supports the need for improved guidance that addresses this common area of practice and the development of alternative care pathways that may be used by ambulance clinicians for patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 14 publications
6
92
0
Order By: Relevance
“…A UK-based qualitative study of decision-making in emergency ambulance clinicians identified themes such as lack of experience, patient views, insufficient information, anxiety over litigation, lack of access to the patients' medical records and bystander expectation as factors influencing the rate of transfer to hospital in this group of patients (Burrell et al, 2013). Many paramedics feel transport to hospital is both clinically safer and a lower risk medico-legally.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A UK-based qualitative study of decision-making in emergency ambulance clinicians identified themes such as lack of experience, patient views, insufficient information, anxiety over litigation, lack of access to the patients' medical records and bystander expectation as factors influencing the rate of transfer to hospital in this group of patients (Burrell et al, 2013). Many paramedics feel transport to hospital is both clinically safer and a lower risk medico-legally.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In the UK, nearly all emergency calls for seizures lead to the dispatch of an ambulance, and a recent study in one UK ambulance study showed that 75% of these patients are transported to hospital (Dickson et al, 2015). Most suspected seizures have stopped by the time the ambulance or paramedics arrive on the scene (Burrell, Noble, & Ridsdale, 2013;Dickson et al, 2017;O'Hara et al, 2015) and many of these patients do not require transport to hospital. 'Reducing the rate of ambulance 999 calls that result in transportation to A&E' is an NHS Commissioning for Quality and Innovation (CQUIN) indicator (NHS England, 2016) and the ambulance service has tried to develop guidelines to support this aim.…”
mentioning
confidence: 99%
“…A detailed study on safety and decision-making by ambulance staff highlighted that, as the need to reduce transports to hospital increases, the requirement for appropriate training and education to equip ambulance clinicians for this role also increases. 176 Two studies on decision-making by ambulance staff for patients with epilepsy 174 and elderly fallers 175 both identified a need for additional training and support to aid safe decision-making, as did one Canadian study that focused on out-of-hospital management of patients with long-term conditions. 182 …”
Section: Safety and Decision-makingmentioning
confidence: 99%
“…Issues about effects of integration with the wider urgent and emergency care system on successful implementation and, in particular, the need to have clear information about patients and about access to alternative care pathways for patients have also been raised. 150,174,176 Other relevant issues identified which impede patient management out of hospital include the conflicting demands of maintaining operational performance and meeting response-time targets (which reduces opportunities for training), barriers between professional groups, a continuing perception that the ambulance service is still primarily a transport service and fear of litigation which is associated with complex decision-making. 174,176 …”
Section: Implementation Of Initiativesmentioning
confidence: 99%
“…This is supported by a study of non-conveyance in the ambulance service for epilepsy, where ambulance crew were concerned about litigation and therefore transported people to hospitals. 69 Additionally, hospital admission has been seen as the only option for ED management of people with mental health problems in rural areas in Australia. 70 …”
mentioning
confidence: 99%